The statement that describes the transformation of the graph of function f onto the graph of function g is:
The graph shifts 5 units left and 3 units up.
The given functions are:
f(x) = (x-4) + 3
g(x) = (x+1) + 6
Comparing the functions f(x) = (x-4) + 3 and g(x) = (x+1) + 6
Difference between f(x) and g(x) on the x-axis = 1 - (-4) = 5
Difference between f(x) and g(x) on the y-axis = 6 - 3 = 3
From the comparison made above, we can conclude that:
The graph of f(x) is shifted to the left by 5 units to form g(x)
The graph of f(x) is shifted up by 3 units to form g(x
Learn more on transformation here: https://brainly.com/question/10222182